Electrochemical DNA Biosensor Based on Poly(allylamine hydrochloride) Modified Screen Printed Electrode - Azah Yusof, Nor (Asian Journal of Chemistry, 2011)
An electrochemical method was used to characterize the interaction between Hoechst 33258 and the short DNA sequence related to E. coli lac gene. The probe ssDNA was immobilized on poly(allylamine hydrochloride) via physical adsorption and covalent attachment. The voltammetric signals of Hoechst 33258 have been investigated using screen printed electrode. The interaction of Hoechst 33258 with ssDNA and dsDNA has been studied and proven to have a promising strategy in improving the selectivity of the DNA sensor. The extent of hybridization was evaluated on the basis of the difference between signals of Hoechst 33258 with a probe DNA before and after hybridization with the target ssDNA. Control experiments with noncomplementary were performed to test the selectivity of the developed DNA biosensor. The redox current was linearly related to the concentration of the target ssDNA from 1.5-6 μM with a detection limit of 0.6 μM.